A conserved structural mechanism of NMDA receptor inhibition: A comparison of ifenprodil and zinc - Sirrieh, Rita E. (J Gen Physiol, 2015)
N-methyl-d-aspartate (NMDA) receptors, one of the three main types of ionotropic glutamate receptors (iGluRs), are involved in excitatory synaptic transmission, and their dysfunction is implicated in various neurological disorders. NMDA receptors, heterotetramers typically composed of GluN1 and GluN2 subunits, are the only members of the iGluR family that bind allosteric modulators at their amino-terminal domains (ATDs). We used luminescence resonance energy transfer to characterize the conformational changes the receptor undergoes upon binding ifenprodil, a synthetic compound that specifically inhibits activation of NMDA receptors containing GluN2B. We found that ifenprodil induced an overall closure of the GluN2B ATD without affecting conformation of the GluN1 ATD or the upper lobes of the ATDs, the same mechanism whereby zinc inhibits GluN2A. These data demonstrate that the conformational changes induced by zinc and ifenprodil represent a conserved mechanism of NMDA receptor inhibition. Additionally, we compared the structural mechanism of zinc inhibition of GluN1–GluN2A receptors to that of ifenprodil inhibition of GluN1–GluN2B. The similarities in the conformational changes induced by inhibitor binding suggest a conserved structural mechanism of inhibition independent of the binding site of the modulator.